2022
DOI: 10.1021/acs.iecr.1c05026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bubble Collapse Combined with Oxidants on the Benzamide by Molecular Dynamics Simulation

Abstract: The combined use of hydrodynamic cavitation technology and H2O2 to treat organic wastewater can not only reduce the treatment time and energy consumption but can also achieve better degradation effects. Models containing different concentrations of H2O2 are established in this study to grasp the effect of H2O2 concentration on the bubble collapse process and benzamide degradation and the relationship among the mechanical, thermal, and chemical effects in the degradation stage. The transferable interatomic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…), and lattice Boltzman (for example, Shan et al) have been used for simulating multidimensional cavity collapse simulations. Some attempts are also made using molecular dynamics (Wei et al). Considering the extreme pressure and temperature generated during cavity collapse and associated uncertainties in estimating physicochemical properties, one-dimensional models of cavity collapse based on the Rayleigh-Plasset type of equations appear to be a pragmatic choice at the moment.…”
Section: Current Status Of Modeling Of Hydrodynamic Cavitation Reacto...mentioning
confidence: 99%
See 1 more Smart Citation
“…), and lattice Boltzman (for example, Shan et al) have been used for simulating multidimensional cavity collapse simulations. Some attempts are also made using molecular dynamics (Wei et al). Considering the extreme pressure and temperature generated during cavity collapse and associated uncertainties in estimating physicochemical properties, one-dimensional models of cavity collapse based on the Rayleigh-Plasset type of equations appear to be a pragmatic choice at the moment.…”
Section: Current Status Of Modeling Of Hydrodynamic Cavitation Reacto...mentioning
confidence: 99%
“…Several different approaches like volume of fluid (for example, Orthaber et al 41 ), smooth particle hydrodynamics (for example, Patinõ-Narinõ et al 42 ), and lattice Boltzman (for example, Shan et al 43 ) have been used for simulating multidimensional cavity collapse simulations. Some attempts are also made using molecular dynamics (Wei et al 44 ).…”
Section: Cavity Dynamics Modelsmentioning
confidence: 99%
“…Amides are important and widely used organic compounds in agriculture and industry. The major degradation intermediate of flonicamid, 4-trifluoromethylnicotinamide (TFNA-AM), is a chordotonal organ modulator insecticide. , Acrylamide (ACM) is a monomer of synthetic plastics and is widely applied in the industry as a binder, thickener, and flocculant. Benzamide (BAM) is widely used in the industrial production of dyestuffs, pharmaceuticals, and pesticides . However, Taylor-Wells et al reported that TFNA-AM is toxic to mice.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of ACM at a sand-and-gravel mine in Minnesota was up to 280 ng/L . Residues of ACM and BAM are widely distributed in industrial wastewater, and their direct discharge into the environment may cause hazards to animals. , Thus, treatment and removal of these hazardous amides is imperative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation